2010
DOI: 10.1093/annonc/mdq220
|View full text |Cite
|
Sign up to set email alerts
|

Survival differences among women with de novo stage IV and relapsed breast cancer

Abstract: This large cohort study provides further insight into the natural history of relapsed and de novo stage IV breast cancer. DFI plays an important role in the prognosis for patients with relapsed breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
191
3
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(221 citation statements)
references
References 15 publications
21
191
3
6
Order By: Relevance
“…El CM se presenta en la mayoría de los casos como una enfermedad localizada, sin embargo, hasta 30% de las pacientes pueden tener una recidiva de la enfermedad [10][11][12] . La presencia de enfermedad metastásica al debut, es un evento poco frecuente 10 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El CM se presenta en la mayoría de los casos como una enfermedad localizada, sin embargo, hasta 30% de las pacientes pueden tener una recidiva de la enfermedad [10][11][12] . La presencia de enfermedad metastásica al debut, es un evento poco frecuente 10 .…”
Section: Discussionunclassified
“…La presencia de enfermedad metastásica al debut, es un evento poco frecuente 10 . En nuestro Centro de Cáncer correspondió a menos de 4% del total de tumores invasores, un número similar a lo reportado en otras series 10,11 . El estudio del perfil de expresión génica en CM evidencia la existencia de una enfermedad heterogénea.…”
Section: Discussionunclassified
“…11 As a result, some cases that might have been assigned as stage IIIc in countries that adhered to criteria in the sixth 10 Overall, the proportion of patients in this study with known HR status who had a primary diagnosis of HR-positive LA/MBC was lower (7.8%) than in previously published estimates (approximately 13%-17%). [6][7][8] However, the generalizability of the previous findings is limited, because they were derived from a small number of patient records. In addition, the range of years and geographic regions included in these studies differed from the present study, and comparisons should therefore be interpreted with caution.…”
Section: Esther Bastiaannet Et Almentioning
confidence: 99%
“…Studies of small retrospective databases have reported that of all patients with known HR status, approximately 13% to 17% had a primary diagnosis of HR-positive advanced disease (LA/MBC). [6][7][8] However, these studies did not assess subsequent therapy in this patient group, and, to our knowledge, a comprehensive evaluation of the size of this patient population has not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies 8,10,15,16 have also reported a range of prognostic factors for women with metastatic breast cancer, including factors such as age at diagnosis, hormone receptor status, human HER2 status, and site of metastases, for predicting survival from the time of metastases. In a cohort of 1,038 women with relapsed mBC, Largillier et al 16 reported that age at initial diagnosis, site of metastasis, and hormone receptor status were independent prognostic factors for survival following the development of metastatic disease.…”
mentioning
confidence: 99%